Enhancing the chemotherapeutic efficacy of platinum prodrug nanoparticles and inhibiting cancer metastasis by targeting iron homeostasis. Issue 6 (4th May 2020) - Ding, Fang; Zhang, Lingpu; Chen, Hao; Song, Haiqin; Chen, Shiguo; Xiao, Haihua
Abstract : Combination of cisplatin prodrug nanoparticles and Dp44mT results in enhanced anticancer and anti-metastatic efficiencies. Abstract : Iron plays important roles in tumor growth and metastasis, and iron depletion has become a new therapeutic strategy for iron overload cancers. Cisplatin is widely applied in the clinical therapy of various malignancies, but it has no inhibitory effect on cancer metastasis. In the present study, we found that the combination of cisplatin and iron chelator Dp44mT resulted in enhanced cell apoptosis as well as attenuated cell mobility and migration in vitro . Next, we developed a nano-carrier system to promote intracellular drug accumulation and reduce the side effects in cancer cells. Results showed that the as-synthesized nanoparticles (NPs) exhibited excellent antitumor efficiency when combined with Dp44mT. In breast tumor-bearing mice, the combination of the NPs and Dp44mT dramatically prevented orthotopic mammary tumor growth and inhibited metastasis via downregulation of VEGFα, MMP2 and Vimentin. In conclusion, as a versatile nano-platform for the combination of chemotherapy and iron chelators, the current design holds great potential for metastasis-inhibited cancer therapy.